Discussion between alternative processing and preservation technologies and their application in beverages: A review. Issue 1 (28th April 2017) - Rascon Escajeda, Luis Felipe; Cruz Hernandez, Mario; Rodriguez Jasso, Rosa María; Charles Rodriguez, Ana Veronica; Robledo Olivo, Armando; Contreras Esquivel, Juan Carlos; Belmares Cerda, Ruth
Abstract: The alternative technologies discussed in this review are able to eliminate pathogenic bacteria while retaining bioactive compounds such as anthocyanins, phenols, pigments, and vitamins, improve the extraction processes of fruit or vegetable juices. The use of nonthermal processing technologies in beverages might provide a higher quality value to the final product and consumers tended to prefer more natural products with minimum preservative substances. This review is analyze and discuss the advantages and disadvantages of alternative technologies applied in beverages, evaluating the parameters that can optimize beverage processing such as time, temperature, pressure, frequency, tension, among others. Additionally, finding solutions to beverage processing issues will be considered analyzing the results obtained with other applied methods, and an overview of new strategies such as microfiltration or the combination of two alternative technologies to improve the quality of the final product will also be evaluated. Practical applications: The applications of alternative technologies mentioned in this article, are a feasible option for the preservation of beverages in the area of industry. The capacity of each of them has been demonstrated, in addition to the use of microfiltration and ultrafiltration, but the combination between them sounds very encouraging to achieve the quality and safety of beverages, with an extended shelf life and greater protection of its main components. This provides a wide range of research opportunities for any type of beverage.